O professor de língua inglesa: suas crenças sobre a formação superior e a prática em sala de aula - Rocha, Judite Queiroz da (2023)
This study is limited to investigating the beliefs of English language teachers who work in schools in the state of Rondônia, about higher education training to teach English and their practices in the classroom. The general objective of this research was to investigate, systematize and analyze the beliefs of English teachers regarding higher education training for teaching English, classroom practices and possible impacts on the teaching and learning process. The choice for this approach is justified by the context in which it was applied and the fact that no specific studies on the subject were found in the region, as it is essential to know the reality experienced by these teachers in order to contribute to the changes that if necessary. The theoretical foundation on beliefs is delimited by studies by Barcelos (1995, 2000, 2001, 2004, 2006, 2007, 2011, 2013, 2015). The qualitative-interpretive research, part of the line of research Constitution and interpretation of text and speech, had data collected through an electronic form, applied to 37 English teachers in the state of Rondônia, via WhatsApp. The data collected in this study leads to the understanding of the relevant role of beliefs in the process of training and performance of IL teachers, since they influence the pedagogical practice experienced by these professionals and their contribution to the process of formation of theoretical-practical knowledge of the teacher, making them transform their practices into reflective actions. Studies on beliefs are extremely important and must be part of the actions of teachers in service or in training. Through this study it was possible to investigate, systematize and analyze the participants' beliefs. Furthermore, it aimed to collaborate, through discussions and reflections developed, with theoretical and practical subsidies, for the improvement of courses, personal training initiatives for FL (English) teachers, professionals in service who invest in continued training and researchers involved with themes covered here, in addition to making contributions to applied research.